Expression and visualization of Green Fluorescent Protein (GFP) in Neurospora crassa - Michael Freitag; Lynda M Ciuffetti; Eric U Selker (Fungal Genetics Reports, 2001)
We report the first successful imaging of GFP expression in Neurospora crassa. GFP was expressed under the control of the heterologous ToxA promoter from Pyrenophora tritici-repentis in transformants carrying multiple or single copies of the GFP construct. GFP was also detected in ascospores but not during earlier stages of the sexual cycle.